Hypothetical learning trajectory in microbiology course through argumentation-based inquiry learning - Evi Roviati; Ria Yulia Gloria; Rizki Sukma Wijaya (University of Muhammadiyah Malang, 2024)
The application of effective teaching methods needs to be implemented to improve the quality of microbiology education which can empower important competencies in the current era. This study aims to analyze the application and trajectory of argumentation-based inquiry learning through the application of microbiology lectures. This research uses research design methods consisting of preliminary design steps, teaching experiments and retrospective analysis. The source of the data comes from student learning activities in argumentation-based inquiry learning implemented in microbiology courses. The results showed that the learning trajectory of Hypothetical Learning Trajectory (HLT) in microbiology lectures with an argumentation-based inquiry model was in accordance with the stages of student research ranging from determining research themes, compiling proposals, designing and implementing data collection, analyzing data, discussing research results, writing research reports to conducting scientific publications in journals. Students who carry out microbiology lectures using argumentation-based inquiry learning through the implementation of different research in the field of microbiology experience a similar learning trajectory so that a specific and distinctive set of Hypothetical Learning Trajectory (HLT) can be formulated.